2013
DOI: 10.1007/s00299-013-1445-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural and physiological characterization during wheat pericarp development

Abstract: The cytological and physiological features of developing wheat pericarp were clearly characterized in this report. Our results may be helpful to articulate the functions of pericarp during the seed development. Although wheat pericarp has been well studied, knowledge of the sequence of events in the process of pericarp development is incomplete. In the present study, the structural development process of wheat (Triticum aestivum L.) pericarp was investigated in detail using resin microtomy and microscopy. Chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 19 publications
6
50
2
Order By: Relevance
“…Previous studies indicated that wheat pericarp, which develops from the ovary wall, consists of epicarp, mesocarp and endocarp . Endocarp, the chlorophyll‐containing layer, is composed of tube cells (TC) and cross cells (CC) . Starch granules accumulated in various cells in pericarp at different developmental stages.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that wheat pericarp, which develops from the ovary wall, consists of epicarp, mesocarp and endocarp . Endocarp, the chlorophyll‐containing layer, is composed of tube cells (TC) and cross cells (CC) . Starch granules accumulated in various cells in pericarp at different developmental stages.…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of ear photosynthesis to grain filling in wheat and barley was estimated to be between 10% and 76%, and, of this, 33– 43% has been attributed to pericarp photosynthesis (Caley et al 1990). In wheat, photosynthetic activity peaked at about 15–20 DAF, coinciding with maximum Chl content in the pericarp green layer (Caley et al 1990, Xiong et al 2013). In rice, pericarp photosynthesis was reported in the grains of transgenic rice plants with the C4- Pdk gene of maize (Fukayama et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…1e), showing that starch mainly accumulated in the endosperm, while pericarp was stained decreasingly with I 2 /KI, indicating gradual disappearance of the starch accumulated in pericarp (Xiong et al 2013a). During 0-12 DAA, the crease region including vascular bundle, chalaza, and nucellar projection were increasingly stained with 2,3,5-triphenyl-2H-tetrazolium chloride, indicating that dehydrogenase activity increased after anthesis and attained a maximum at 12 DAA (Fig.…”
Section: Resultsmentioning
confidence: 93%